Pengaruh Pengetahuan Perpajakan, E-Filing dan Kualitas Pelayanan Relawan Pajak Terhadap Kepatuhan WPOP - Nakhwatunnisa, Haulah; Febriani Adriana, Tasya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research uses quantitative methods and data collection techniques through surveys which are carried out by collecting samples from the population using questionnaires as a data measuring tool. The population in this research is all taxpayers with active status in Cirebon City, namely 232 taxpayers. The sample used in this research was 70 taxpayers using a purposive sampling method. The data analysis techniques used in this research include multiple linear regression equation analysis, t test, F test, coefficient of determination and classical assumption test with the help of data processing using the Statistical Product and Service Solution (SPSS) Version 26 application. The research results show that Tax Knowledge has a positive and significant effect on Individual Taxpayer Compliance, while E-Filing has an effect but is not significant on Individual Taxpayer Compliance and the Quality of Tax Volunteer Services does not have a significant effect on Individual Taxpayer Compliance. The results of the simultaneous test (f test) show a significant value of 0.000 < 0.05 and a calculated F value of 10.36 > F table 2.74, meaning that Tax Knowledge, E-Filing, and Tax Volunteer Service Quality simultaneously influence Taxpayer Compliance. Private at the Tax Center of IAIN Syekh Nurjati Cirebon. The R square result is 0.3202, so it is known that there is a simultaneous relationship between Tax Knowledge, E-Filing, and Tax Volunteer Service Quality on Individual Taxpayer Compliance at the Tax Center of IAIN Syekh Nurjati Cirebon of 32.02%.